The turns of the road. The right to decide and the principles - Bastida Freixedo, Xacobe (EUNOMÍA. Revista en Cultura de la Legalidad, 2020)
This paper explores the possibilities offered by the Spanish legal system regarding the recognition to the Right to Decide. Beginning with a criticism to the report of J.Mª Vilasojana- «Democracy and Right to Decide», published in this magazine- in which the adequacy of that right to the principles of the Constitution of 1978 is defended, I intend to prove, firstly, that the constitutional reform is not, in any case, a suitable way to achieve the introduction to the right to decide; secondly, using constitutionalism as a theory able to integrate the right to decide in the Spanish legal system – as it happens with any other legal route – is bounded to failure since it requires the political will of the majority parties which, as they have declared, it will never exist.